Change of jurisdiction by the prosecutor: problems of law enforcement - V. V. Romaniuk (Law and Safety)
The novelties of the criminal procedural legislation regarding the expansion of the grounds for the prosecutor to change the jurisdiction of criminal offenses have been analyzed. It has been established that in the conditions of martial law, liability as one of the general provisions of pre-trial investigation has lost its primary categorical meaning, the essence of which is to determine the competence of the pre-trial investigation body based on the set of legally established features of criminal proceedings. With the application of the comparative method, an analysis of the powers of the prosecutor regarding their change of liability in criminal offenses with the beginning of the military aggression of the Russian Federation before and after the entry into force of the amendments to Part 5 of Article 36 of the CCP of Ukraine has been carried out. It has been recognized that in the conditions of martial law, each body of pre-trial investigation is universal through the prism of the institution of accountability, since pre-trial investigation can be carried out in any criminal offense by the decision of the authorized prosecutor.